2004
DOI: 10.1002/jmv.20107
|View full text |Cite
|
Sign up to set email alerts
|

Clinically‐based determination of safe DNAemia cutoff levels for preemptive therapy or human cytomegalovirus infections in solid organ and hematopoietic stem cell transplant recipients

Abstract: Transplantation Centers using human cytomegalovirus (HCMV) antigenemia-based preemptive therapy will need to replace in the near future the antigenemia assay with a more standardized and automatable assay, such as a molecular assay quantifying HCMV DNA in blood (DNAemia). Thus, in view of replacing antigenemia with clinically safe cutoff values, DNAemia levels corresponding to antigenemia cutoffs guiding HCMV preemptive therapy were determined retrospectively in solid organ and hematopoietic stem cell transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
(25 reference statements)
0
37
0
Order By: Relevance
“…DNAemia was quantified weekly or bi-weekly upon occurrence of active HCMV infection. Pre-emptive antiviral therapy was given to Tx patients reaching a DNAemia cut-off of 300 000 DNA copies ml À1 whole blood (Lilleri et al, 2004;Gerna et al, 2007Gerna et al, , 2011 and consisted of iv ganciclovir (GCV) at a dosage of 5 mg kg À1 twice a day, or oral valganciclovir (VGCV), 900 mg twice a day. Antiviral therapy was continued until the virus disappeared from blood.…”
Section: Methodsmentioning
confidence: 99%
“…DNAemia was quantified weekly or bi-weekly upon occurrence of active HCMV infection. Pre-emptive antiviral therapy was given to Tx patients reaching a DNAemia cut-off of 300 000 DNA copies ml À1 whole blood (Lilleri et al, 2004;Gerna et al, 2007Gerna et al, , 2011 and consisted of iv ganciclovir (GCV) at a dosage of 5 mg kg À1 twice a day, or oral valganciclovir (VGCV), 900 mg twice a day. Antiviral therapy was continued until the virus disappeared from blood.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of this protein can occur independently of viral DNA replication. 23 Based on this knowledge and the results of a receiveroperator curve analysis, 9,10 we recently terminated a trial in young HSCT recipients in which a DNAemia cutoff of 10 000 copies per ml blood was compared to initial antigenemia positivity for starting preemptive therapy of HCMV infection. 11 Results of this study showed that a DNAemia cutoff can be safely adopted to guide preemptive therapy of HCMV infection in HSCT recipients (no case of HCMV disease was observed), while the number of patients requiring treatment with respect to antigenemia was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a recent study conducted by our group in which an ultrasensitive diagnostic assay (immediate-early mRNA detection by nucleic acid sequence-based amplification) was compared with antigenemia, it was shown that this sensitive assay led to treatment of a higher number of patients with respect to antigenemia. 8 At this time, based on a retrospective analysis of DNAemia levels in HSCT recipients undergoing antigenemia-guided surveillance of HCMV infection, 9,10 we decided to compare a predetermined cutoff of 10 000 copies per ml whole blood with first antigenemia positivity, for preemptive therapy guidance of HCMV infection in a population of pediatric HSCT recipients. DNAemia was chosen for cutoff definition instead of antigenemia, since the assay is partially automatable and standardizable, and more closely reflects the actual viral replication in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This technique offers some advantages over others PCR methods, including increased precision, accuracy, reproducibility and a shorter turnaround time. To date, the clinical utility of using the RT-PCR test to guide preemptive therapy in transplant recipients has been mainly studied in SCT recipients Boeckh M, 2009;Gerna et al, 2008;Gimeno et al, 2008;Harrington et al, 2007;Kalpoe et al, 2004;Lilleri et al, 2004;Limaye et al, 2001;Machida et al, 2000;Ruell et al, 2007;Verkruyse et al, 2006). However, it has not been established a cutoff threshold for initiating antiviral therapy against CMV probably due to the significant differences between the different techniques used to determine the CMV viral load.…”
Section: Introductionmentioning
confidence: 99%